Novel nanostructured-TiO2 materials for the photocatalytic reduction of CO2 greenhouse gas to hydrocarbons and syngas. (1st June 2015) - Akhter, Parveen; Hussain, Murid; Saracco, Guido; Russo, Nunzio
Graphical abstract: Highlights: Novel nanostructured-TiO2 s were used for CO2 reduction to hydrocarbons and syngas. Meso. TiO2 showed a higher production and better reaction kinetics and stability. There was competitive adsorption of CO2 and H2 O vapors on surface of the catalyst. UV light, H2 O/CO2 ratios and catalyst shapes were optimized to improve products. Partial saturation of active adsorption sites and O2 produced caused deactivation. Abstract: In the current work an attempt has been made to synthesize novel high surface area nano-TiO2 materials (titanium dioxide nanoparticles/TNPs and nanostructured or mesoporous titanium dioxide using KIT-6 silica template/Meso. TiO2 ) in order to establish the photocatalytic reduction of CO2 greenhouse gas in the presence of H2 O vapor to produce hydrocarbons and syngas. The synthesized materials have been characterized through N2 -adsorption/desorption, X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and ultraviolet–visible (UV–Vis) spectroscopy analysis techniques. The TNPs consists of an average 11 nm of TiO2 particles, shows a higher surface area of 151 m 2 /g than the commercial Aeroxide P25 TiO2 (53 m 2 /g), and also demonstrates an enhanced adsorption capacity. However, the Meso. TiO2 has shown a higher surface area (190 m 2 /g) and mesoporosity (4 nm pores) than the TNPs and Aeroxide P25 TiO2, as confirmed by the characterizations. In the reaction, the TNPs with the enhanced adsorption capability, due to the high surface area and smaller nano-sized particle morphology, showed a higher syngas (CO, H2 ) production than the commercial Aeroxide P25 TiO2 . However, the novel Meso. TiO2 showed more hydrocarbons (CH4, CH3 OH) and a higher syngas production together with better reaction kinetics and stability due to its better characteristics than the commercial Aeroxide P25 TiO2 . The key parameters that affect the activity have been optimized to increase fuel production. The reaction mechanism indicates competitive adsorption of CO2 and H2 O vapors on the catalyst surface. The key parameters including the UV light source and UV intensity, H2 O/CO2 ratios and catalyst shapes influence the catalytic performance, and therefore, these parameters have been optimized to increase the fuel products. Partial saturation of the active adsorption sites and the oxygen produced are the possible causes of the deactivation, however, the catalysts can be regenerated quickly through a simple evaporation technique.